Interweaving autonomous learning and peer-tutoring in coaching efl student-teachers (2009)
In this article we share the findings on the exploration of undergraduate efl (English as a Foreign Language) student-teachers’ professional preparation and autonomous practices. Participants were tutees who attended tutorial sessions with peers in higher semesters. In this context, tutoring was based on a model we designed. As the model was implemented, they collected information by means of multiple qualitative research instruments. Results indicate that tutees’ learning process was strongly influenced by their personality and attitudes. Similarly, tutees expanded their views in regard to the English language, its learning, and their communicative competence. Finally, we pinpoint some considerations for others interested in adopting this pedagogical strategy. Key words: Peer tutoring, university tutoring, autonomous learning, independent work En este artículo compartimos hallazgos relacionados con la preparación profesional y las prácticas autónomas de estudiantes de inglés en un programa de licenciatura. Los participantes tutorados asistían a sesiones tutoriales con compañeros en semestres superiores. En este contexto, la tutoría se basó en un modelo que diseñamos. Durante la implementación del modelo se recogió información a través de múltiples instrumentos cualitativos de investigación. Los resultados revelan que el proceso de aprendizaje de los tutorados se vio fuertemente influenciado por su personalidad y sus actitudes. Asimismo, los tutorados ampliaron sus puntos de vista sobre la lengua inglesa, su aprendizaje y su competencia comunicativa. Finalmente, señalamos algunas consideraciones para los interesados en adoptar esta estrategia pedagógica Palabras clave: Tutoría entre compañeros, tutoría a nivel universitario, aprendizaje autónomo, trabajo independiente